The Impact of the Russia-Ukraine War on Grace Indonesia-Russia Diplomacy Relations - Junaedi Junaedi (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Indonesia's relations with Russia-Ukraine have been very cordial, especially with Russia, both in terms of economic relations as well as defense and security, where Indonesia often buys weapons and combat equipment from Russia. The Impact of the Russo-Ukrainian War on the Friendship of Indonesia-Russia Diplomatic Relations. Data analysis was carried out using an analysis of the Impact of the Russo-Ukrainian War on the Friendship of Indonesia-Russia Diplomatic Relations. The purpose of this study is to examine and analyze the Impact of the Russo-Ukrainian War on the Friendly Relations of Indonesia-Russia Diplomatic Relations. As for the benefits of this research Academically, this research is useful regarding the Impact of the Russo-Ukrainian War on the Peace of Indonesia-Russia Diplomatic Relations, while theoretically, this research can enrich the repertoire of literature in terms of the study of the Impact of the Russo-Ukrainian War on the Peace of Diplomatic Relations between Indonesia and Russia.